2019
DOI: 10.1111/jcmm.14194
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and tenovin‐6 synergistically induces apoptosis through LKB1‐independent SIRT1 down‐regulation in non‐small cell lung cancer cells

Abstract: Sirtuin 1 (SIRT1) is known to play a role in a variety of tumorigenesis processes by deacetylating histone and non‐histone proteins; however, antitumour effects by suppressing SIRT1 activity in non‐small cell lung cancer (NSCLC) remain unclear. This study was designed to scrutinize clinicopathological significance of SIRT1 in NSCLC and investigate effects of metformin on SIRT1 inhibition. This study also evaluated new possibilities of drug combination using a SIRT1 inhibitor, tenovin‐6, in NSCLC cell lines. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“…Previously, the SIRT family has been reported to serve a critical part in the process of tumorigenesis (25)(26)(27). Each individual SIRT may act either as a tumor suppressor or an oncogene in different types of malignancies, potentially via tumor-associated signaling pathways or mitosis regulation (13,28,29). However, the specific association between SIRTs and OC remains controversial, and remains to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the SIRT family has been reported to serve a critical part in the process of tumorigenesis (25)(26)(27). Each individual SIRT may act either as a tumor suppressor or an oncogene in different types of malignancies, potentially via tumor-associated signaling pathways or mitosis regulation (13,28,29). However, the specific association between SIRTs and OC remains controversial, and remains to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs included in our study were divided into 7 parts according to their clinical characteristics. As we can see in the picture, most of the circRNAs are significantly related to lymphatic metastasis and TNM stage cancer cell [118]. has_circ_001569 preforms its function by miRNA-148a, enhancing Wnt/β-catenin pathway associated gene expression [119].…”
Section: Interactions Of Mrnas In Different Circrna-mirna-mrna Networkmentioning
confidence: 99%
“…Tenovin-6, an inhibitor of both SIRT1 and SIRT2, in combination with metformin, an antidiabetic drug and mTOR signaling pathway inhibitor, caused cell growth inhibition and induced apoptosis in lung cancer cells (Lee et al, 2019). Additionally, a preclinical study identified the synergistic interaction of ricolinostat and ibrutinib the first-in-class BTK (Bruton's tyrosin kinase) inhibitor in a large panel of lymphoma cell lines and in a xenograft model of lymphoma.…”
Section: Selective Hdacis In Combination With Tyrosine Kinase Pathwaymentioning
confidence: 99%